2005
DOI: 10.1029/2005gl024370
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation controls Sahel greening trend

Abstract: [1] The Sahel region has been identified as a ''hot spot'' of global environmental change, but understanding of the roles of different climatic and anthropogenic forcing factors driving change in the region is incomplete. We show that a process-based ecosystem model driven by climatic and atmospheric CO 2 data alone closely reproduces the satelliteobserved greening trend of the Sahel vegetation and its interannual variability between 1982 and 1998. Changes in precipitation were identified as the primary driver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
164
2
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 225 publications
(195 citation statements)
references
References 23 publications
28
164
2
1
Order By: Relevance
“…Hickler et al (2005) showed that a positive trend in satellite-measured NDVI greenness through the 1980s and 1990s was best explained by a positive trend in precipitation over this period. Expanding this analysis to 2002, using a spatially explicit approach, accounting for additional regional effects of human land use, did not significantly improve agreement between modelled vegetation patterns and satellite observations (Seaquist et al, 2009 Fig.…”
Section: Inter-annual Greenness Variability 1982-2006mentioning
confidence: 99%
See 1 more Smart Citation
“…Hickler et al (2005) showed that a positive trend in satellite-measured NDVI greenness through the 1980s and 1990s was best explained by a positive trend in precipitation over this period. Expanding this analysis to 2002, using a spatially explicit approach, accounting for additional regional effects of human land use, did not significantly improve agreement between modelled vegetation patterns and satellite observations (Seaquist et al, 2009 Fig.…”
Section: Inter-annual Greenness Variability 1982-2006mentioning
confidence: 99%
“…Results from the model have been compared to ecosystem flux measurements, site measurements and satellite-based proxies of NPP, leaf area index (LAI) and biomass, spanning many of the world's biomes (Morales et al, 2005;Hickler et al, 2005Hickler et al, , 2006Hély et al, 2006;Smith et al, 2008;Ahlström et al, 2012a). LPJ-GUESS has been shown to be better than LPJ-DGVM at predicting potential natural vegetation, e.g.…”
Section: Dgvmmentioning
confidence: 99%
“…Changes in precipitation were identified as the primary driver of the greening trend of the Sahel vegetation and its interannual variability between 1982 and 1998 (Hickler et al, 2005), although Anyamba and Tucker (2005) emphasize that the NDVI time series commenced ARTICLE IN PRESS during a historically intense drought (the early 1980s) and that the recent gradual recovery has likely not returned vegetation to pre-drought conditions of the 1950s and 1960s. However, the resilience of vegetation to rainfall is not evident everywhere and the idea of ''greening Sahel'' has been challenged by some authors (Hiernaux and Turner, 2002;Hountondji et al, 2006;Ozer and Ozer, 2005).…”
Section: Article In Pressmentioning
confidence: 99%
“…In addition to influences from anthropogenic activity (e.g. changes in land use), vegetation changes in the region have been linked to changes in recorded climatic conditions, including the trend and interannual variability in precipitation (Herrmann et al, 2005;Hickler et al, 2005;Zhou et al, 2014), which in turn have been related to decadal-scale changes in regional circulation (Camberlin et al, 2001;Giannini et al, 2003). On longer timescales, anthropogenic climate change has the potential to cause profound structural and compositional changes in vegetation over Africa (Sitch et al, 2008;Scheiter and Higgins, 2009).…”
Section: Introductionmentioning
confidence: 99%